Biology and Breeding of Food Legumes - Pratap, Aditya; Kumar, Jitendra; Ebooks Corporation (Wallingford : CABI, 2011)
Food legumes are important constituents of the human diet and animal feed where they are crucial to a balanced diet, supplying high quality proteins. These crops also play an important role in low-input agricultural production systems by fixing atmospheric nitrogen. Despite systematic and continuous breeding efforts through conventional methods, substantial genetic gains have not been achieved. With the rise in demand for food legumes/pulses and increased market value of these crops, research has focused on increasing production and improving the quality of pulses for both edible and industrial purposes. "Biology and Breeding of Food Legumes" covers the history, origin and evolution, botany, breeding objectives and procedures, nutritional improvement, industrial uses and post-harvest technology and also recent developments made through biotechnological intervention. This title is suitable for academic libraries and researchers in crop science and agriculture.
Contenido: 15 Breeding for Biotic Stresses16 Breeding for Abiotic Stresses; 17 Legume Improvement in Acidic and Less Fertile Soils; 18 Molecular Breeding Approach in Managing Abiotic Stresses; 19 Trait Mapping and Molecular Breeding; 20 Improving Protein Content and Nutrition Quality; 21 Underutilized Food Legumes: Potential for Multipurpose
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CULTIVOS ALIMENTICIOS -- MEJORAMIENTO DE LAS ESPECIES; LEGUMBRES; LEGUMBRES COMO ALIMENTO; LEGUMBRES -- MEJORAMIENTO DE LAS ESPECIES